Effects of Exercise on Neuropathy in Streptozotocin-Induced Diabetic Rats - Lee, Eui Chang (Ann Rehabil Med, 2017)
OBJECTIVE: To evaluate the effects of early regular exercise and to assess the electrophysiological and histopathological findings of the rat tail nerve in relation to the timing of exercise training for swimming exercise in rats with diabetic neuropathy. METHODS: We used 70 Sprague-Dawley male rats, and the experimental group comprised 60 rats, and the control group comprised 10 rats. Diabetes was induced by intraperitoneal injection of streptozotocin. Blood glucose concentrations were measured in tail vein blood samples. The experimental group was divided into 6 subgroups according to insulin treatment and swimming exercise: group 1, diabetic control; group 2, insulin treated; group 3, insulin untreated with early swimming exercise; group 4, insulin treated and early swimming exercise; group 5, insulin treated and late swimming exercise; and group 6, insulin untreated with late swimming exercise. Sensory and motor nerve conduction studies were performed weekly up to the 13th week using rat tail nerves. The effect on structural diabetic neuropathy was assessed by morphometry and ultrastructural examination of the rat tail nerve fiber at the 14th week. RESULTS: An exercise effect was observed in the insulin treated groups, but it was not observed in the insulin untreated groups. The sensory nerve conduction study in the rat tail revealed significantly prolonged latency and decreased amplitude in groups 1 and 6, and a further delay was observed in group 5 when compared to group 4. Decreased thickness of myelin was found in groups 1 and 6 through morphometry. CONCLUSION: Early regular exercise programs in addition to conventional insulin treatment may retard the progression of diabetic peripheral neuropathy.